2022
DOI: 10.1186/s12909-022-03362-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: a catalyst for the digitization of surgical teaching at a German University Hospital

Abstract: Background The summer semester 2020, had to be restructured due to the SARS-CoV-2 pandemic and the associated contact restrictions. Here, for the first time, the established lectures in lecture halls and small group seminars could not be conducted in presence as usual. A possible tool for the implementation of medical teaching, offers the use of eLearning, online webinars and learning platforms. At present it is unclear how the SARS-CoV-2 pandemic will affect surgical teaching, how digitization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The pandemic has forced most universities around the world to-all of a sudden-switch to distance education, with extremely limited preparation possibilities and resources. The sudden change made it impossible to hold contact hours or to send the necessary equipment for the students to practice at home [9][10][11][12]. Although the pandemic catalyzed this process, we believe the lessons learned and the newly developed methodologies could be applied for further emergency situations, resource-limited settings, or even in the regular curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has forced most universities around the world to-all of a sudden-switch to distance education, with extremely limited preparation possibilities and resources. The sudden change made it impossible to hold contact hours or to send the necessary equipment for the students to practice at home [9][10][11][12]. Although the pandemic catalyzed this process, we believe the lessons learned and the newly developed methodologies could be applied for further emergency situations, resource-limited settings, or even in the regular curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, online communication platforms have provided an important approach to continue medical education. While lectures or interactive seminars can be easily delivered online, it has been challenging to conduct surgical training (requiring a high level of teacher–student interactions) online or via pre-recorded videos [ 14 17 , 28 ]. Although, scattered studies reported feasibility of online teaching for practical surgical skills, video-based education constitutes a passive learning mode and will not be able to substitute hands-on courses [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a current publication by Kofoed et al illustrated that performance of students randomly assigned to an online introductory economic class was lower than their peers who participated in in-person courses [ 13 ]. Furthermore, a recent German survey of medical students investigating the effects of e-learning for teaching surgical skills emphasized that practical surgical competencies cannot be adequately represented by online offers [ 14 ]. Notwithstanding, online teaching of basic surgical skills emerged to be effective and therefore shows potential to overcome the limits imposed by the COVID-19 crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Almost 25% of the studies focus on the development of virtualization in education (n=32). This trend seems natural given that educational institutions often manifest the extensive advantages of employing virtual computing (Wolf et al, 2022;Xu et al, 2022;Yee et al, 2022). Slightly over 20% of the studies target virtualization in the field of machine learning (n=27).…”
Section: Discussionmentioning
confidence: 99%